Kajian Literatur Mengenai Kebijakan Pendidikan Karakter dan Pengaruhnya terhadap Prestasi Akademik Siswa - Kuat Ngimron; Eny Kadarwati; Jalaludin Jalaludin (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
This literature review aims to analyze and synthesize the findings from various studies on character education policy in Indonesia and how it affects student academic achievement. Within the national education system, the Strengthening Character Education policy has been a major focus. However, the relationship between character implementation and academic achievement remains debated. The research method employs a qualitative approach with content analysis techniques on scientific literature from 2015-2025 sourced from national and international journals and official policy documents from the Ministry of Education, Culture, Research, and Technology. Data analysis was conducted through content analysis techniques encompassing reduction, data presentation, and conclusion drawing. Overall, the results indicate that character education policy has an indirect positive effect on academic achievement. Mediating variables, enhanced character traits such as discipline, responsibility, and integrity, increase student engagement in the learning process. The reviewed studies emphasize that consistent policy implementation, character integration in every subject, and comprehensive school environment support are critical components determining success. Nevertheless, there are significant research gaps in terms of standardizing credible character evaluation instruments and measuring long-term impact. According to this research, character strengthening is a prerequisite for creating a good learning environment, which in turn improves academic achievement. Therefore, in the future, more in-depth longitudinal empirical research is needed.